Pengaruh Ekspor, Impor, dan Inflasi Terhadap Nilai Tukar di Indonesia - Maylafensya Rahmasari Tuto Hali; Salsa Nabila Nasution; Nabilla Permata Asri (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to investigate the impact of exports, imports and inflation on the exchange rate in Indonesia. By analyzing the interaction between these three variables, we can better understand how these factors are interconnected and how they influence the stability of this country's currency. The method used in writing this research journal is a quantitative regression method relying on data from Bank Indonesia, Trade Map, World Bank Database, and the Central Statistics Agency. This method is carried out by determining or analyzing the character of the relationship between one dependent variable and a series of other or independent variables. High import values ​​can cause a deficit in the trade balance and result in increased demand for foreign currency. The increase in the value of exports causes the supply of foreign currency in the domestic market to increase and can strengthen the value of the Rupiah. Inflation fluctuations in Indonesia are influenced by various factors which can show that the higher the inflation rate, the higher the exchange rate.